The Promise of Scriptural Reasoning - Hardy, Daniel W. (Modern theology, 2006)
This Response reintroduces Scriptural Reasoning as portrayed in the essays, showing their various readings and reasonings and how they shed light on SR, while also identifying some lacunae in and between them. The different strengths of these views interact with each other in a highly dynamic and sustaining practice of reading and reasoning Scriptures together, where there is a high degree of mutually responsible hospitality and the possibility of achieving a complex harmony. In conclusion, three tasks for the future of SR are identified: concentrating on the seminal features of the Abrahamic traditions, targeting them and auditing SR performance.